Uma revista digital interativa como recurso para abordar volume e capacidade no ensino fundamental - Schardosim, Erica da Silva (2023)
Nowadays, it is still common to observe the excessive use of the traditional teaching method in the educational context, even after so many technological advances at the turn of the century. In this sense, it is necessary to encourage changes, put into practice the new tools that are available to teachers to make classes more attractive and motivational, with the aim that students are more active in their teaching-learning process, no longer just knowledge receivers. Specifically with regard to teaching mathematics in elementary school, it is common to use only a notebook and pencil to solve exercises with memorized formulas, with no applicability in everyday situations. As a result, the present study aims to develop, put into practice and evaluate an interactive educational product, an interactive digital magazine, which addresses the concepts of volume and capacity. It is expected that the magazine will serve as support, providing the teacher with virtual teaching material to use in all their classes that address these objects of knowledge in the ninth years, the school education level of Elementary School Final Years. The digital magazine was built using two platforms: Canva® allowed the creation of the layout of all pages of the magazine in PDF, and Flipsnack® made it possible to make the pages available in digital magazine format. The magazine also uses the following digital tools to carry out activities: Wordwall®, Mentimeter®, Pixton®, Kahoot®, Thunkable®, Google Forms®, YouTube® and Lucidchart®. The magazine presents, throughout its pages, several activities that were programmed to approach the contents gradually, following a didactically designed order to develop specific skills. To apply and evaluate the educational product, a didactic sequence was created based on David Ausubel's Theory of Meaningful Learning and the use of TDICs. The didactic sequence uses the various activities available in the interactive digital magazine. It was structured into ten meetings and the study's guiding question was: How can the use of an interactive digital magazine that addresses the concepts of volume and capacity promote meaningful learning of these contents? The research developed is of a qualitative, participatory and action nature, using the following instruments for data collection: logbook, activities developed by students during the application of the didactic sequence and a questionnaire to evaluate the educational product by the students. The application of the interactive digital magazine took place in a ninth-year class of Elementary School Final Years, in the second semester of 2022, in a private school located in the municipality of Itajaí/SC. Analysis of the data collected in the study indicates that students demonstrated interest and motivation during classes, regarding the use of the digital magazine, as it presents different digital tools and is a different form of teaching, favoring the desire to study and learning. The results indicate that the magazine can be of great use in aiding the teaching activities of mathematics teachers, in approaching the proposed contents. In this sense, it can be suggested that teaching methodologies using TDICs are potential tools for achieving meaningful learning, as they arouse the student's interest, making them want to learn, which is one of the fundamental requirements for the development of learning. significant. This dissertation accompanies the educational product, the interactive digital magazine entitled "DESCOMPLICANDO Volume e Capacity", in addition to an e-book that helps and teaches teachers how to build their own version of the magazine.